Comparing performance of cross-laminated timber and reinforced concrete walls - Bahrami, Alireza; Nexén, Oliver; Jonsson, Jonas (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this research is to specify the differences between the performance of cross-laminated timber (CLT) and reinforced concrete (RC) walls. The study is done by using the finite element structural analysis and design software, StruSoft FEM-Design, in order to model, analyse and design a reference building located in the city of Gävle in Sweden.
Keywords: cross-laminated timber wall; reinforced concrete wall; load-bearing; Finite Element Method (FEM); utilisation ratio